The Construction of Tarāduf between Khauf and Khasyah in the Qur’an: Semantic Analysis and Interpretive Implications - Afkar Azizi; Misnawati Misnawati (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the construction of al-tarāduf between the words khauf and khasyyah in the Qur’an through semantic analysis and its implications for interpretation. Both words are often translated as “fear,” yet they possess different nuances of meaning when analyzed contextually. This research aims to explore the meanings of khauf and khasyyah, analyze their usage in Qur’anic verses, and identify the interpretive implications arising from the differences between the two terms. This study employs a qualitative method with a library research approach by examining classical and contemporary tafsir literature as well as linguistic studies related to Qur’anic semantics. The findings indicate that khauf refers more to general fear arising from perceived danger or threat, whereas khasyah denotes fear rooted in knowledge, reverence, and awareness of the greatness of Allah. These differences demonstrate that the Qur’an does not use synonymous words randomly, but rather places each word according to its semantic and contextual function. Therefore, understanding the distinction between khauf and khasyah is important in order to avoid simplification of meaning and to strengthen accuracy in interpreting Qur’anic verses.